Extraction and Purification of Collagen from Marine Squid Uroteuthis Duvauceli: Life Sciences-Biotechnology for prospective Medical Science - Jency George; Dr. Manjusha W. A. (International Journal of Life Science and Pharma Research, 2022)
Collagen is a protein, which plays a significant role in the development of tissues and organs. These are used for cosmetic surgery and as wound healing aids in burn patients, remaking of bone and a wide assortment of dental, orthopedic and surgical purposes. These days’ collagen is isolated from calf, porcine tissue and so forth. But it can cause the onset of diseases such as, for example, Bovine spongiform encephalopathy (BSE), Transmissible spongiform encephalopathy (TSE), Foot-and-mouth illness (FMD), and so forth and furthermore cultural and social concerns. As another option, collagen can be separated from marine squid. The aim of the present work is to isolate and partially characterize the collagen from the marine squid, Uroteuthis duvauceli. The confined collagen was evaluated by utilizing Bradford test and partially purified by using gel filtration on a Sepharose 4B column. These filtered collagens were affirmed by SDS PAGE. These days industrially accessible collagen in the market are costly and are not affordable to the common people. The present data on collagens from the marine squid, could help the future endeavors to unwind the therapeutically significant, more secure collagens from marine squid for their utilization in the biomedical field.